2021
DOI: 10.1017/s0376892921000011
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception, trust and support for wildlife reintroduction and conservation

Abstract: Summary Wildlife reintroduction projects often face resistance from local residents who see potential conflicts with the species or lack trust or confidence in the agencies and professionals involved in reintroduction. Yet the linkages between trust, confidence, risk perceptions, attitudes towards the species and local support for its reintroduction are not well known. The Dual-Mode Model of Cooperation and Cognitive Hierarchy Model were theoretical frameworks used to shed light on these linkages by explori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
1
17
0
2
Order By: Relevance
“…HWIs are receiving increasing attention from a conservation perspective, possibly as a result of biodiversity decline and changing attitudes and values towards wildlife (Echeverri et al, 2018;Watkins et al, 2021). HWIs can be both positive and negative, can be influenced by context and by previous experience, trends in society and individual processes (Johansson et al, 2016; see Frank and Glikman, 2019 for a review).…”
Section: Human-wildlife Interactions In the Context Of Conservation T...mentioning
confidence: 99%
See 1 more Smart Citation
“…HWIs are receiving increasing attention from a conservation perspective, possibly as a result of biodiversity decline and changing attitudes and values towards wildlife (Echeverri et al, 2018;Watkins et al, 2021). HWIs can be both positive and negative, can be influenced by context and by previous experience, trends in society and individual processes (Johansson et al, 2016; see Frank and Glikman, 2019 for a review).…”
Section: Human-wildlife Interactions In the Context Of Conservation T...mentioning
confidence: 99%
“…Recommendations: These mechanisms should address residents' concerns effectively, consistently and transparently; Ensuring such processes are known to local people and diverse interest groups (Watkins et al, 2021).…”
Section: Identifying and Integrating Interest Groups In A Participati...mentioning
confidence: 99%
“…Being a reintroduction project a management strategy, the agencies, programs, and projects leading need to acknowledge its relevance, sensitivity, and timeconsumption, to make it a routine, which conducted in a safe interpersonal and institutional environment promotes learning and trust among participants and prevents (reduces or mitigates) conflicts. Trust and confidence in management agencies are important to reduce risk perception and to gain support for reintroduction (Watkins et al, 2021).…”
Section: Actions Using a Human Dimensions Approach And The Lack Of Detailmentioning
confidence: 99%
“…Seddon et al (2007) reviewed articles published between 1990 and 2005 involving wildlife reintroduction and found that only 4% considered certain aspects of human dimensions (HD), such as people's attitudes toward reintroductions. Watkins et al (2021) highlight that besides the growing actions for species reintroduction, the human dimensions of humanbirds interactions and the reintroduction implications for the communities are still little known and explored.…”
Section: Introductionmentioning
confidence: 99%
“…Each tribal community and buffalo program has unique needs and objectives, through which opportunities exist to support the eco-cultural restoration of bison (Johns, 2020). Engaging communities in co-designing and planning associated with buffalo programs can build social trust and help mitigate the risk of negative public perception (Watkins et al, 2021). To that end, as demonstrated in the case studies, each Tribe has initiated community engagement activities to gain public support and rebuild a constituency for bison, based upon the perception that reconnecting the community with bison herds will provide multiple benefits (Haggerty et al, 2017;Wilkins et al, 2019).…”
Section: Community-based Restorationmentioning
confidence: 99%